In vitro digestion of nanoscale starch particles and evolution of thermal, morphological, and structural characteristics. (December 2016) - Liu, Chengzhen; Jiang, Suisui; Han, Zhongjie; Xiong, Liu; Sun, Qingjie
Abstract: In vitro digestions of starch nanocrystals (SNCs), prepared by acid hydrolysis of native starch and starch nanoparticles (SNPs) fabricated by self-assembly of short glucan chains, were investigated for kinetics of enzymatic hydrolysis. Their thermal, morphological, and structural properties during amylolysis were also compared. The kinetics of enzymatic hydrolysis indicated that the hydrolysis rate of SNPs was lowest in that of SNCs, cooked starch, and native starch. Onset, peak, conclusion temperatures, and enthalpy of gelatinization of SNPs and SNCs decreased during digestion. The A-type crystallization of SNCs contributed to their higher rate of hydrolysis than that of SNPs, which was B-type. The relative crystallinity of SNCs during hydrolysis decreased but that of SNPs increased. The results suggest that SNPs exhibit higher resistance to digestion than SNCs. This finding provides information for diverse potential applications of SNCs and SNPs. Graphical abstract: Highlights: The hydrolysis rate of SNPs was lower than that of SNCs. The gelatinization temperature of SNCs and SNPs decreased after amylolysis. The relative crystallinity of SNCs via hydrolysis decreased but that of SNPs increased. The size of the SNCs decreased but that of SNPs increased after amylolysis.